Access to improved water source and satisfaction with services: Evidence from rural Ethiopia - Abebaw, Degnet; Tadesse, Fanaye; Mogues, Tewodaj (International Food Policy Research Institute, 2011)
In recent years access to safe and reliable water supplies has received increased government attention in Ethiopia. As a result, the national coverage rate for this service has gradually improved. Yet millions of people in rural areas still do not get drinking water from an improved water source. While expanding improved water source schemes is generally essential, it is equally important to ensure that the schemes have increased users' satisfaction with water quality and availability for everyday use. Using household survey data and employing univariate and bivariate probit models, this paper attempts to investigate the effect of access to an improved water source on users' satisfaction with both quality and availability of water. The study findings suggest that access to an improved water source significantly raised household satisfaction with both quality and availability of water. However, the effect of the improved water source on users' satisfaction was slightly lower for water availability than for water quality.